L’empire de l’imaginaire : la fin du monde et son rapport à l’histoire dans l’œuvre de Lucian Boia - Aurélien Portelli (Amnis)
The imaginary of the end of the world is one of the main keys to understanding the work of Lucian Boia. For this historian, the narratives of the end of the world refer, beyond their obvious differences, to the same archetypal structures, which he essentially associates with the imaginaries of divination and escape. Collapsology, which emerged in France in 2015, echoes the prophecies of doom that have been announcing the end of the world for thousands of years. The scale and reality of the threats identified by collapse theorists nevertheless tend to disqualify the analogy between their prediction and end-of-the-world myths based on religious beliefs or science fiction scenarios. From this point of view, all the ends of the world could not be equal. However, this argument does not allow us to dismiss so quickly what the narrative of the collapse owes to the history of the imaginary and its structures. Boia's theoretical framework, far from being invalidated by the discourse of the collapsologists, makes it possible, on the contrary, to give their prediction a historical depth, by resituating it in a genealogy of myths of the end of the world and by linking it to imaginaries of crisis that manifest themselves on various scales of time.